A Descriptive Study of Transplant Coordinator Job Satisfaction. (September 2021) - Lerret, Stacee M.; Stendahl, Gail; Alexander, Susan; Pendegraft, Amanda; Hoy, Haley
Introduction: Substantial growth in the field of transplantation in recent years has increased the need for transplant coordinators. The growing need for these highly skilled clinicians warrants a review of characteristics that increase job satisfaction, an important consideration for transplant centers. Research question: The study described transplant coordinators' perceptions of job satisfaction in their current positions. Design: This study evaluated transplant coordinator job satisfaction conducted on 3 separate occasions at US geographically diverse sites. Two instruments, the Vermont Nurses: Job Analysis and Retention Survey and an investigator-designed role and demographic survey, were used to capture study participants' attitudes regarding elements of job satisfaction, design, and involvement. Results: Demographic characteristics of study participants (N = 133) reveal a largely female population (n = 113, 85%) employed full time (n = 124, 93%) in a hospital setting (n = 106, 80%). Scores for items related to job satisfaction, design, and involvement were generally positive. Participants reported being less satisfied for characteristics including promotion opportunities, fringe benefits, and attention to career development provided by employers. Conclusion: As annual rates of transplants continue to increase across the United States, the need for growing and retaining talented staff in transplant care settings is even more critical. Results of the study suggest that while transplant coordinators remain largely satisfied with the challenges and personal fulfillment associated with their positions, opportunities for professional development may improve retention and recruitment. Specifically, supporting career development and providing formalized evaluation and supervision were identified as areas of improvement within this specialized group of clinicians.